Interaction of Composite Material-Based Geopolymer with Soil in Road Pavement using Finite Element Method - Irnawan, Muhammad Chofi; Zaika, Yulvi; Munawir, As'ad (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Geopolymer is an eco-friendly binder derived from natural or artificial precursors such as fly ash and slag. The purpose of this research is to investigate the response of Recycled Concrete Aggregate (RCA) with Geobead (GB) filler based geopolymer to soil in terms of vertical deflection values using Axisymmetric model Finite Element Method (FEM), which compared with unbound materials such as granular base courses or bound materials such as cement-treated base (CTB), lean concrete (LC), and foamed concrete (FC). The model was loaded with incremental static loading due to vehicle wheel load, and the pavement behavior, such as vertical surface deflection at the base layer with bonded and unbonded materials, was analyzed. The analysis indicated that using bonded materials based on geopolymer resulted in smaller deflection values when compared to base course materials. The addition of geobead affects the unit weight reduction of the pavement material. However, increasing the rise in geobead content results in a vertical deflection value due to reduced bonding between RCA grains. The deflection value of the RCA-GB-based geopolymer in all variations of GB content is below that of the granular materials. However, geopolymer-based materials with the addition of geobeads resulted in greater deflection than CTB, LC, and FC.